Reliable electrocortical dynamics of target-directed pass-kicks - Piskin, Daghan Yuksel; Büchel, Daniel; Lehmann, Tim; Baumeister, Jochen (Cognitive Neurodynamics)
Abstract Football is one of the most played sports in the world and kicking with adequate accuracy increases the likelihood of winning a competition. Although studies with different target-directed movements underline the role of distinctive cortical activity on superior accuracy, little is known about cortical dynamics associated with kicking. Mobile electroencephalography is a popular tool to investigate cortical modulations during movement, however, inherent and artefact-related pitfalls may obscure the reliability of functional sources and their activity. The purpose of this study was therefore to describe consistent cortical dynamics underlying target-directed pass-kicks based on test–retest reliability estimates. Eleven participants performed a target-directed kicking task at two different sessions within one week. Electroencephalography was recorded using a 65-channel mobile system and behavioural data were collected including motion range, acceleration and accuracy performance. Functional sources were identified using independent component analysis and clustered in two steps with the components of first and subsequently both sessions. Reliability estimates of event-related spectral perturbations were computed pixel-wise for participants contributing with components of both sessions. The parieto-occipital and frontal clusters were reproducible for the same majority of the sample at both sessions. Their activity showed consistent alpha desyhronization and theta sychnronisation patterns with substantial reliability estimates revealing visual and attentional demands in different phases of kicking. The findings of our study reveal prominent cortical demands during the execution of a target-directed kick which may be considered in practical implementations and provide promising academic prospects in the comprehension and investigation of cortical activity associated with target-directed movements.
Keywords: Exercise Neuroscience

The Mode of Endurance Exercise Influences Changes in EEG Resting State Graphs among High-Level Cross-Country Skiers - Büchel, Daniel; Torvik, Per Øyvind; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Weaker Quadriceps Corticomuscular Coherence in Individuals Following ACL Reconstruction during Force Tracing - Sherman, David A.; Baumeister, Jochen; Stock, Matt S.; Murray, Amanda M.; Bazett-Jones, David M.; Norte, Grant E. (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

The Mode of Endurance Exercise Influences Changes in EEG Resting State Graphs among High-Level Cross-Country Skiers. - Büchel, Daniel; Torvik, PØ; Lehmann, Tim; Sandbakk, Ø; Baumeister, Jochen (Med Sci Sports Exerc)

Inhibition of Motor Planning and Response Selection after Anterior Cruciate Ligament Reconstruction. - Sherman, DA; Baumeister, Jochen; Stock, MS; Murray, AM; Bazett-Jones, DM; Norte, GE (Med Sci Sports Exerc)

Mobile Electroencephalography Reveals Differences in Cortical Processing During Exercises With Lower and Higher Cognitive Demands in Preadolescent Children - Becker, Linda; Büchel, Daniel; Lehmann, Tim; Kehne, Miriam; Baumeister, Jochen (Pediatric Exercise Science)
Purpose : The aim of this study was to examine whether cortical activity changes during exercise with increasing cognitive demands in preadolescent children. Method : Twenty healthy children (8.75 [0.91] y) performed one movement game, which was conducted with lower and higher cognitive demands. During a baseline measurement and both exercise conditions, cortical activity was recorded using a 64-channel electroencephalographic system, and heart rate was assessed. Ratings of perceived excertion and perceived cognitive engagement were examined after each condition. To analyze power spectral density in the theta, alpha-1, and alpha-2 frequency bands, an adaptive mixture independent component analysis was used to determine the spatiotemporal sources of cortical activity, and brain components were clustered to identify spatial clusters. Results : One-way repeated-measures analyses of variance revealed significant main effects for condition on theta in the prefrontal cluster, on alpha-1 in the prefrontal, central, bilateral motor, bilateral parieto-occipital, and occipital clusters, and on alpha-2 in the left motor, central, and left parieto-occipital clusters. Compared with the lower cognitive demand exercise, cortical activity was significantly higher in theta power in the prefrontal cluster and in alpha-1 power in the occipital cluster during the higher cognitive demand exercise. Conclusion : The present study shows that exercise complexity seems to influence cortical processing as it increased with increasing cognitive demands.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; Pediatrics; Perinatology and Child Health

A Comparison of the Most Intense Periods (MIPs) During Competitive Matches and Training Over an 8-Week Period in a Male Elite Field Hockey Team - Büchel, Daniel; Döring, Michael; Baumeister, Jochen (Journal of Science in Sport and Exercise)
Abstract Purpose Wearables serve to quantify the on-court activity in intermittent sports such as field hockey (FH). Based on objective data, benchmarks can be determined to tailor training intensity and volume. Next to average and accumulated values, the most intense periods (MIPs) during competitive FH matches are of special interest, since these quantify the peak intensities players experience throughout the intermittent matches. The aim of this study was to retrospectively compare peak intensities between training and competition sessions in a male FH team competing in the first german division. Methods Throughout an 8-week in-season period, 372 individual activity datasets (144 datasets from competitive sessions) were recorded using the Polar Team Pro sensor (Kempele, Finland). MIPs were calculated applying a rolling window approach with predefined window length (1–5 min) and calculated for Total distance, High-Intensity-Running distance (> 16 km/h), Sprinting distance (> 20 km/h) and Acceleration load. Significant differences between training and competition MIPs were analysed through non-parametric statistical tests ( P < 0.05). Results Analyses revealed higher MIPs during competition for all considered outcomes ( P < 0.001). Effect size estimation revealed strongest effects for sprinting distance ( d = 1.89 to d = 1.22) and lowest effect sizes for acceleration load ( d = 0.92 to d = 0.49). Conclusion The present findings demonstrate that peak intensities during training do not reach those experienced during competitive sessions in a male FH team. Training routines such as manipulations of court-dimensions and team sizes might contribute to this discrepancy. Coaches should compare training and competition intensities to recalibrate training routines to optimize athletes’ preparation for competition.
Keywords: Nutrition and Dietetics; Rehabilitation; Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; Physiology

Increased Cognitive Demands Affect Agility Performance in Female Athletes - Implications for Testing and Training of Agility in Team Ball Sports - Büchel, Daniel; Gokeler, Alli; Heuvelmans, Pieter; Baumeister, Jochen (Perceptual and Motor Skills)
Agility, a key component of team ball sports, describes an athlete´s ability to move fast in response to changing environments. While agility requires basic cognitive functions like processing speed, it also requires more complex cognitive processes like working memory and inhibition. Yet, most agility tests restrict an assessment of cognitive processes to simple reactive times that lack ecological validity. Our aim in this study was to assess agility performance by means of total time on two agility tests with matched motor demands but with both low and high cognitive demands. We tested 22 female team athletes on SpeedCourt, using a simple agility test (SAT) that measured only processing speed and a complex agility test (CAT) that required working memory and inhibition. We found excellent to good reliability for both our SAT (ICC = .79) and CAT (ICC =.70). Lower agility performance on the CAT was associated with increased agility total time and split times ( p < .05). These results demonstrated that agility performance depends on the complexity of cognitive demands. There may be interference-effects between motor and cognitive performances, reducing speed when environmental information becomes more complex. Future studies should consider agility training models that implement complex cognitive stimuli to challenge athletes according to competitive demands. This will also allow scientists and practitioners to tailor tests to talent identification, performance development and injury rehabilitation.
Keywords: Sensory Systems; Experimental and Cognitive Psychology

Cortical responses to sport-specific stimuli in a standing stop signal task - Scharfen, Hans-Erik; Lehmann, Tim; Büchel, Daniel; Baumeister, Jochen (Psychology of Sport and Exercise)
Keywords: Applied Psychology

Ecological Validity in Exercise Neuroscience Research: A Systematic Investigation - Chang, M.; Büchel, Daniel; Reinecke, K.; Lehmann, T.; Baumeister, Jochen (European Journal of Neuroscience)
Keywords: General Neuroscience

Surface Instability Modulates Cortical Information Processing In Multi-Joint Compound Movements - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen (Medicine &Science in Sports& Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Changes In Eeg Microstate Patterns Following Exhaustive Treadmill Exercise When Employing Reduced Channel Resolution - Büchel, Daniel; Allen, Carlos; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine &Science in Sports& Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Surface Instability Modulates Cortical Information Processing In Multi-Joint Compound Movements - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen

Continuous table tennis is associated with processing in frontal brain areas: an EEG approach - Visser, Anton; Büchel, Daniel; Lehmann, Tim; Baumeister, Jochen (Experimental Brain Research)
Abstract Coordinative challenging exercises in changing environments referred to as open-skill exercises seem to be beneficial on cognitive function. Although electroencephalographic research allows to investigate changes in cortical processing during movement, information about cortical dynamics during open-skill exercise is lacking. Therefore, the present study examines frontal brain activation during table tennis as an open-skill exercise compared to cycling exercise and a cognitive task. 21 healthy young adults conducted three blocks of table tennis, cycling and n-back task. Throughout the experiment, cortical activity was measured using 64-channel EEG system connected to a wireless amplifier. Cortical activity was analyzed calculating theta power (4–7.5 Hz) in frontocentral clusters revealed from independent component analysis. Repeated measures ANOVA was used to identify within subject differences between conditions (table tennis, cycling, n-back; p < .05). ANOVA revealed main-effects of condition on theta power in frontal ( p < .01, η p 2 = 0.35) and frontocentral ( p < .01, η p 2 = 0.39) brain areas. Post-hoc tests revealed increased theta power in table tennis compared to cycling in frontal brain areas ( p < .05, d = 1.42). In frontocentral brain areas, theta power was significant higher in table tennis compared to cycling ( p < .01, d = 1.03) and table tennis compared to the cognitive task ( p < .01, d = 1.06). Increases in theta power during continuous table tennis may reflect the increased demands in perception and processing of environmental stimuli during open-skill exercise. This study provides important insights that support the beneficial effect of open-skill exercise on brain function and suggest that using open-skill exercise may serve as an intervention to induce activation of the frontal cortex.
Keywords: General Neuroscience

Surface Instability Modulates Cortical Information Processing In Multi-Joint Compound Movements - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Effects of surface instability on cortical information processing during multi- joint compound movements: an exploratory EEG study - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen

Performance and Brain Activity in Older Adults while Playing Leaning and Stepping Exergames - Müller, Helen Martha; Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen

Changes In Eeg Microstate Patterns Following Exhaustive Treadmill Exercise When Employing Reduced Channel Resolution - Büchel, Daniel; Allen, Carlos; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Ecological validity in exercise neuroscience research: A systematic investigation - Chang, Melissa; Büchel, Daniel; Reinecke, Kirsten; Lehmann, Tim; Baumeister, Jochen (European Journal of Neuroscience)
Keywords: General Neuroscience

Exploring intensity-dependent modulations in EEG resting-state network efficiency induced by exercise - Büchel, Daniel; Sandbakk, Øyvind; Baumeister, Jochen (European Journal of Applied Physiology)
Abstract Purpose Exhaustive cardiovascular load can affect neural processing and is associated with decreases in sensorimotor performance. The purpose of this study was to explore intensity-dependent modulations in brain network efficiency in response to treadmill running assessed from resting-state electroencephalography (EEG) measures. Methods Sixteen trained participants were tested for individual peak oxygen uptake (VO 2 peak ) and performed an incremental treadmill exercise at 50% (10 min), 70% (10 min) and 90% speed VO 2 peak (all-out) followed by cool-down running and active recovery. Before the experiment and after each stage, borg scale (BS), blood lactate concentration (B La ), resting heartrate (HR rest ) and 64-channel EEG resting state were assessed. To analyze network efficiency, graph theory was applied to derive small world index (SWI) from EEG data in theta, alpha-1 and alpha-2 frequency bands. Results Analysis of variance for repeated measures revealed significant main effects for intensity on BS, B La , HR rest and SWI. While BS, B La and HR rest indicated maxima after all-out, SWI showed a reduction in the theta network after all-out. Conclusion Our explorative approach suggests intensity-dependent modulations of resting-state brain networks, since exhaustive exercise temporarily reduces brain network efficiency. Resting-state network assessment may prospectively play a role in training monitoring by displaying the readiness and efficiency of the central nervous system in different training situations.

Stance leg and surface stability modulate cortical activity during human single leg stance - Büchel, Daniel; Lehmann, Tim; Ullrich, Sarah; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Experimental Brain Research)
Abstract Mobile Electroencephalography (EEG) provides insights into cortical contributions to postural control. Although changes in theta (4–8 Hz) and alpha frequency power (8–12 Hz) were shown to reflect attentional and sensorimotor processing during balance tasks, information about the effect of stance leg on cortical processing related to postural control is lacking. Therefore, the aim was to examine patterns of cortical activity during single-leg stance with varying surface stability. EEG and force plate data from 21 healthy males (22.43 ± 2.23 years) was recorded during unipedal stance (left/right) on a stable and unstable surface. Using source-space analysis, power spectral density was analyzed in the theta, alpha-1 (8–10 Hz) and alpha-2 (10–12 Hz) frequency bands. Repeated measures ANOVA with the factors leg and surface stability revealed significant interaction effects in the left ( p = 0.045, η p 2 = 0.13) and right motor clusters ( F = 16.156; p = 0.001, η p 2 = 0.41). Furthermore, significant main effects for surface stability were observed for the fronto-central cluster (theta), left and right motor (alpha-1), as well as for the right parieto-occipital cluster (alpha-1/alpha-2). Leg dependent changes in alpha-2 power may indicate lateralized patterns of cortical processing in motor areas during single-leg stance. Future studies may therefore consider lateralized patterns of cortical activity for the interpretation of postural deficiencies in unilateral lower limb injuries.

Functional Cortical Connectivity Related to Postural Control in Patients Six Weeks After Anterior Cruciate Ligament Reconstruction - Lehmann, Tim; Büchel, Daniel; Mouton, Caroline; Gokeler, Alli; Seil, Romain; Baumeister, Jochen (Frontiers in Human Neuroscience)
Whereas initial findings have already identified cortical patterns accompanying proprioceptive deficiencies in patients after anterior cruciate ligament reconstruction (ACLR), little is known about compensatory sensorimotor mechanisms for re-establishing postural control. Therefore, the aim of the present study was to explore leg dependent patterns of cortical contributions to postural control in patients 6 weeks following ACLR. A total of 12 patients after ACLR (25.1 ± 3.2 years, 178.1 ± 9.7 cm, 77.5 ± 14.4 kg) and another 12 gender, age, and activity matched healthy controls participated in this study. All subjects performed 10 × 30 s. single leg stances on each leg, equipped with 64-channel mobile electroencephalography (EEG). Postural stability was quantified by area of sway and sway velocity. Estimations of the weighted phase lag index were conducted as a cortical measure of functional connectivity. The findings showed significant group × leg interactions for increased functional connectivity in the anterior cruciate ligament (ACL) injured leg, predominantly including fronto−parietal [ F (1, 22) = 8.41, p ≤ 0.008, η 2 = 0.28], fronto−occipital [ F (1, 22) = 4.43, p ≤ 0.047, η 2 = 0.17], parieto−motor [ F (1, 22) = 10.30, p ≤ 0.004, η 2 = 0.32], occipito−motor [ F (1, 22) = 5.21, p ≤ 0.032, η 2 = 0.19], and occipito−parietal [ F (1, 22) = 4.60, p ≤ 0.043, η 2 = 0.17] intra−hemispherical connections in the contralateral hemisphere and occipito−motor [ F (1, 22) = 7.33, p ≤ 0.013, η 2 = 0.25] on the ipsilateral hemisphere to the injured leg. Higher functional connectivity in patients after ACLR, attained by increased emphasis of functional connections incorporating the somatosensory and visual areas, may serve as a compensatory mechanism to control postural stability of the injured leg in the early phase of rehabilitation. These preliminary results may help to develop new neurophysiological assessments for detecting functional deficiencies after ACLR in the future.

EEG-derived brain graphs are reliable measures for exploring exercise-induced changes in brain networks - Büchel, Daniel; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Scientific Reports)
Abstract The interaction of acute exercise and the central nervous system evokes increasing interest in interdisciplinary research fields of neuroscience. Novel approaches allow to monitor large-scale brain networks from mobile electroencephalography (EEG) applying graph theory, but it is yet uncertain whether brain graphs extracted after exercise are reliable. We therefore aimed to investigate brain graph reliability extracted from resting state EEG data before and after submaximal exercise twice within one week in male participants. To obtain graph measures, we extracted global small-world-index (SWI), clustering coefficient (CC) and characteristic path length (PL) based on weighted phase leg index (wPLI) and spectral coherence (Coh) calculation. For reliability analysis, Intraclass-Correlation-Coefficient (ICC) and Coefficient of Variation (CoV) were computed for graph measures before (REST) and after POST) exercise. Overall results revealed poor to excellent measures at PRE and good to excellent ICCs at POST in the theta, alpha-1 and alpha-2, beta-1 and beta-2 frequency band. Based on bootstrap-analysis, a positive effect of exercise on reliability of wPLI based measures was observed, while exercise induced a negative effect on reliability of Coh-based graph measures. Findings indicate that brain graphs are a reliable tool to analyze brain networks in exercise contexts, which might be related to the neuroregulating effect of exercise inducing functional connections within the connectome. Relative and absolute reliability demonstrated good to excellent reliability after exercise. Chosen graph measures may not only allow analysis of acute, but also longitudinal studies in exercise-scientific contexts.

Stance leg and surface stability modulate cortical activity during human single leg stance - Büchel, Daniel; Lehmann, Tim; Ullrich, Sarah; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Experimental Brain Research)

PIVOT: A Parsimonious End-to-End Learning Framework for Valuing Player Actions in Handball using Tracking Data - Müller, Oliver; Caron, Matthew; Döring, Michael; Heuwinkel, Tim; Baumeister, Jochen (8th Workshop on Machine Learning and Data Mining for Sports Analytics (ECML PKDD 2021))
Over the last years, several approaches for the data-driven estimation of expected possession value (EPV) in basketball and association football (soccer) have been proposed. In this paper, we develop and evaluate PIVOT: the first such framework for team handball. Accounting for the fast-paced, dynamic nature and relative data scarcity of hand- ball, we propose a parsimonious end-to-end deep learning architecture that relies solely on tracking data. This efficient approach is capable of predicting the probability that a team will score within the near future given the fine-grained spatio-temporal distribution of all players and the ball over the last seconds of the game. Our experiments indicate that PIVOT is able to produce accurate and calibrated probability estimates, even when trained on a relatively small dataset. We also showcase two interactive applications of PIVOT for valuing actual and counterfactual player decisions and actions in real-time.
Keywords: expected possession value; handball; tracking data; time series classification; deep learning

Somatosensory perturbations influence cortical activity associated with single-limb balance performance - Sherman, David A.; Lehmann, Tim; Baumeister, Jochen; Grooms, Dustin R.; Norte, Grant E. (Experimental Brain Research)
Keywords: General Neuroscience

External Focus of Attention Influences Cortical Activity Associated with Single Limb Balance Performance - Sherman, David A; Lehmann, Tim; Baumeister, Jochen; Gokeler, Alli; Donovan, Luke; Norte, Grant E (Physical Therapy)
Abstract Objective External focus (EF) of attention leads to improved balance performance. Consideration of the neuromodulatory effects of EF may inform its clinical utility in addressing neuroplastic impairments after musculoskeletal injuries. We aimed to determine whether electrocortical activity and balance performance changed with attentional foci that prioritized differing sensory feedback and whether changes in electrocortical activity and balance were associated. Methods Individuals who were healthy (n = 15) performed a single-limb balance task under 3 conditions: internal focus (IF), somatosensory focus [EF with a baton (EF-baton)], and visual focus [EF with a laser (EF-laser)]. Electrocortical activity and postural sway were recorded concurrently using electroencephalography and a triaxial force plate. Electroencephalographic signals were decomposed, localized, and clustered to generate power spectral density in θ and α-2 frequency bands. Postural sway signals were analyzed with center-of-pressure sway metrics (eg, area, distance, velocity) and knee angle. The relationship between percent change in clustered brain activity and task performance metrics was assessed. Results Both EF conditions resulted in increased cortical activity and improved balance performance compared to IF. EF-laser had the largest effect, demonstrating increased frontal θ power (d = 0.64), decreased central θ power (d = −0.30), and decreased bilateral motor, bilateral parietal, and occipital α-2 power (d = −1.38 to −4.27) as well as a shorter path distance (d = −0.94) and a deeper (d = 0.70) and less variable (d = −1.15) knee angle than IF. Weak to moderate associations exist between increases in cortical activity and improved balance performance (ρ = 0.405–0.584). Conclusions EF resulted in increased cortical activity associated with cognitive, motor, somatosensory, and visual processing. EF-laser, which prioritized visual feedback, had the largest and broadest effects. Changes in cortical activity resulting from EF were independently associated with improved balance performance. Impact This study demonstrates that goal-oriented attention results in functional increases in brain activity compared to internally directed self-focus. These results suggest EF may target neurophysiologic impairments and improve balance in clinical populations.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation

Functional Cortical Connectivity Related to Postural Control in Patients Six Weeks After Anterior Cruciate Ligament Reconstruction - Lehmann, Tim; Büchel, Daniel; Mouton, Caroline; Gokeler, Alli; Seil, Romain; Baumeister, Jochen (Frontiers in Human Neuroscience)
Whereas initial findings have already identified cortical patterns accompanying proprioceptive deficiencies in patients after anterior cruciate ligament reconstruction (ACLR), little is known about compensatory sensorimotor mechanisms for re-establishing postural control. Therefore, the aim of the present study was to explore leg dependent patterns of cortical contributions to postural control in patients 6 weeks following ACLR. A total of 12 patients after ACLR (25.1 ± 3.2 years, 178.1 ± 9.7 cm, 77.5 ± 14.4 kg) and another 12 gender, age, and activity matched healthy controls participated in this study. All subjects performed 10 × 30 s. single leg stances on each leg, equipped with 64-channel mobile electroencephalography (EEG). Postural stability was quantified by area of sway and sway velocity. Estimations of the weighted phase lag index were conducted as a cortical measure of functional connectivity. The findings showed significant group × leg interactions for increased functional connectivity in the anterior cruciate ligament (ACL) injured leg, predominantly including fronto−parietal [ F (1, 22) = 8.41, p ≤ 0.008, η 2 = 0.28], fronto−occipital [ F (1, 22) = 4.43, p ≤ 0.047, η 2 = 0.17], parieto−motor [ F (1, 22) = 10.30, p ≤ 0.004, η 2 = 0.32], occipito−motor [ F (1, 22) = 5.21, p ≤ 0.032, η 2 = 0.19], and occipito−parietal [ F (1, 22) = 4.60, p ≤ 0.043, η 2 = 0.17] intra−hemispherical connections in the contralateral hemisphere and occipito−motor [ F (1, 22) = 7.33, p ≤ 0.013, η 2 = 0.25] on the ipsilateral hemisphere to the injured leg. Higher functional connectivity in patients after ACLR, attained by increased emphasis of functional connections incorporating the somatosensory and visual areas, may serve as a compensatory mechanism to control postural stability of the injured leg in the early phase of rehabilitation. These preliminary results may help to develop new neurophysiological assessments for detecting functional deficiencies after ACLR in the future.
Keywords: Behavioral Neuroscience; Biological Psychiatry; Psychiatry and Mental health; Neurology; Neuropsychology and Physiological Psychology

Stance leg and surface stability modulate cortical activity during human single leg stance - Büchel, Daniel; Lehmann, Tim; Ullrich, Sarah; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Experimental Brain Research)
Abstract Mobile Electroencephalography (EEG) provides insights into cortical contributions to postural control. Although changes in theta (4–8 Hz) and alpha frequency power (8–12 Hz) were shown to reflect attentional and sensorimotor processing during balance tasks, information about the effect of stance leg on cortical processing related to postural control is lacking. Therefore, the aim was to examine patterns of cortical activity during single-leg stance with varying surface stability. EEG and force plate data from 21 healthy males (22.43 ± 2.23 years) was recorded during unipedal stance (left/right) on a stable and unstable surface. Using source-space analysis, power spectral density was analyzed in the theta, alpha-1 (8–10 Hz) and alpha-2 (10–12 Hz) frequency bands. Repeated measures ANOVA with the factors leg and surface stability revealed significant interaction effects in the left ( p = 0.045, η p 2 = 0.13) and right motor clusters ( F = 16.156; p = 0.001, η p 2 = 0.41). Furthermore, significant main effects for surface stability were observed for the fronto-central cluster (theta), left and right motor (alpha-1), as well as for the right parieto-occipital cluster (alpha-1/alpha-2). Leg dependent changes in alpha-2 power may indicate lateralized patterns of cortical processing in motor areas during single-leg stance. Future studies may therefore consider lateralized patterns of cortical activity for the interpretation of postural deficiencies in unilateral lower limb injuries.
Keywords: General Neuroscience

EEG‑derived brain graphs are reliable measures for exploring exercise‑induced changes in brain networks - Büchel, Daniel; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Scientific Reports)
Keywords: Multidisciplinary

Neurocognitive and Neurophysiological Functions Related to ACL Injury: A Framework for Neurocognitive Approaches in Rehabilitation and Return-to-Sports Tests - Piskin, Daghan Yuksel; Benjaminse, Anne; Dimitrakis, Panagiotis; Gokeler, Alli (Sports Health: A Multidisciplinary Approach)
Context: Only 55% of the athletes return to competitive sports after an anterior cruciate ligament (ACL) injury. Athletes younger than 25 years who return to sports have a second injury rate of 23%. There may be a mismatch between rehabilitation contents and the demands an athlete faces after returning to sports. Current return-to-sports (RTS) tests utilize closed and predictable motor skills; however, demands on the field are different. Neurocognitive functions are essential to manage dynamic sport situations and may fluctuate after peripheral injuries. Most RTS and rehabilitation paradigms appear to lack this aspect, which might be linked to increased risk of second injury. Objective: This systematic and scoping review aims to map existing evidence about neurocognitive and neurophysiological functions in athletes, which could be linked to ACL injury in an integrated fashion and bring an extensive perspective to assessment and rehabilitation approaches. Data Sources: PubMed and Cochrane databases were searched to identify relevant studies published between 2005 and 2020 using the keywords ACL, brain, cortical, neuroplasticity, cognitive, cognition, neurocognition, and athletes. Study Selection: Studies investigating either neurocognitive or neurophysiological functions in athletes and linking these to ACL injury regardless of their design and technique were included. Study Design: Systematic review. Level of Evidence: Level 3. Data Extraction: The demographic, temporal, neurological, and behavioral data revealing possible injury-related aspects were extracted and summarized. Results: A total of 16 studies were included in this review. Deficits in different neurocognitive domains and changes in neurophysiological functions could be a predisposing risk factor for, or a consequence caused by, ACL injuries. Conclusion: Clinicians should view ACL injuries not only as a musculoskeletal but also as a neural lesion with neurocognitive and neurophysiological aspects. Rehabilitation and RTS paradigms should consider these changes for assessment and interventions after injury.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Hamstrings substitution via anteromedial portal with optional anterolateral ligament reconstruction is the preferred surgical technique for anterior cruciate ligament reconstruction: a survey among ESSKA members. - Vascellari, A; Grassi, A; Canata, GL; Zaffagnini, S; Gokeler, A; Jones, H (Knee Surg Sports Traumatol Arthrosc)

Sagittal knee kinematics in relation with the posterior tibia slope during jump landing after an anterior cruciate ligament reconstruction. - Keizer, MNJ; Hijmans, JM; Gokeler, A; Otten, E; Brouwer, RW (J Exp Orthop)

Healthy subjects with lax knees use less knee flexion rather than muscle control to limit anterior tibia translation during landing. - Keizer, MNJ; Hijmans, JM; Gokeler, A; Benjaminse, A; Otten, E (J Exp Orthop)

Functional progression milestones following anterior cruciate ligament reconstruction are more appropriate than time-based criteria: a survey among the ESSKA. - Vascellari, A; Gokeler, A; Grassi, A; Canata, GL; Zaffagnini, S; Jones, H (Knee Surg Sports Traumatol Arthrosc)

Younger age and hamstring tendon graft are associated with higher IKDC 2000 and KOOS scores during the first year after ACL reconstruction. - Magnitskaya, N; Mouton, C; Gokeler, A; Nuehrenboerger, C; Pape, D; Seil, R (Knee Surg Sports Traumatol Arthrosc)

Passing return to sports tests after ACL reconstruction is associated with greater likelihood for return to sport but fail to identify second injury risk. - Welling, W; Benjaminse, A; Lemmink, K; Gokeler, A (Knee)

Balance task difficulty affects postural sway and cortical activity in healthy adolescents. - Gebel, A; Lehmann, T; Granacher, U (Exp Brain Res)

Platelet-rich plasma (PRP) as therapy for cartilage, tendon and muscle damage - German working group position statement. - Tischer, T; Bode, G; Buhs, M; Marquass, B; Nehrer, S; Vogt, S; Zinser, W; Angele, P; Spahn, G; Welsch, GH; Niemeyer, P; Madry, H (J Exp Orthop)

The influence of motor tasks and cut-off parameter selection on artifact subspace reconstruction in EEG recordings - Anders, P; Müller, H; Skjæret-Maroni, N; Vereijken, B; Baumeister, Jochen (Medical & Biological Engineering & Computing)

Modulations of Inter-Hemispherical Phase Coupling in Human Single Leg Stance. - Lehmann, T; Büchel, D; Cockcroft, J; Louw, Q; Baumeister, Jochen (Neuroscience)

Electrocortical dynamics differentiate athletes exhibiting low- and high- ACL injury risk biomechanics. - Bonnette, S; Diekfuss, JA; Grooms, DR; Kiefer, AW; Riley, MA; Riehm, C; Moore, C; Barber Foss, KD; DiCesare, CA; Baumeister, Jochen; Myer, GD (Psychophysiology)

Exploring the phenomenological, environmental, and task-related aspects of the Yips in Tennis, Miniature Golf, Darts, and Archery. - Klämpfl, Martin; Lobinger, Babett; Lehmann, Tim (International Journal of Sport Psychology)

The influence of motor tasks and cut-off parameter selection on artifact subspace reconstruction in EEG recordings - Anders, Phillipp; Müller, Helen Martha; Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen (Medical & Biological Engineering & Computing)
Advances in EEG filtering algorithms enable analysis of EEG recorded during motor tasks. Although methods such as artifact subspace reconstruction (ASR) can remove transient artifacts automatically, there is virtually no knowledge about how the vigor of bodily movements affects ASRs performance and optimal cut-off parameter selection process. We compared the ratios of removed and reconstructed EEG recorded during a cognitive task, single-leg stance, and fast walking using ASR with 10 cut-off parameters versus visual inspection. Furthermore, we used the repeatability and dipolarity of independent components to assess their quality and an automatic classification tool to assess the number of brain-related independent components. The cut-off parameter equivalent to the ratio of EEG removed in manual cleaning was strictest for the walking task. The quality index of independent components, calculated using RELICA, reached a maximum plateau for cut-off parameters of 10 and higher across all tasks while dipolarity was largely unaffected. The number of independent components within each task remained constant, regardless of the cut-off parameter used. Surprisingly, ASR performed better in motor tasks compared with non-movement tasks. The quality index seemed to be more sensitive to changes induced by ASR compared to dipolarity. There was no benefit of using cut-off parameters less than 10.
Keywords: Computer Science Applications; Biomedical Engineering

Modulations of Inter-Hemispherical Phase Coupling in Human Single Leg Stance - Lehmann, Tim; Büchel, Daniel; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Neuroscience)
Keywords: General Neuroscience

Effect of playing position and time on-court on activity profiles in german elite team handball - Büchel, Daniel; Jakobsmeyer, Rasmus; Döring, Michael; Adams, Michael; Rückert, Ulrich; Baumeister, Jochen (International Journal of Performance Analysis in Sport)

Neuroplastic changes in anterior cruciate ligament reconstruction patients from neuromechanical decoupling. - An, YW; DiTrani Lobacz, A; Lehmann, T; Baumeister, Jochen; Rose, WC; Higginson, JS; Rosen, J; Swanik, CB (Scand J Med Sci Sports)

Between-session and inter-rater reliability of the modified tuck jump assessment in healthy adult athletes. - Gokeler, A; Dingenen, B (Phys Ther Sport)

Reply to Koller and Schobersberger: Comment on: "Revised Approach to the Role of Fatigue in Anterior Cruciate Ligament Injury Prevention: A Systematic Review with Meta-analyses". - Benjaminse, A; Webster, KE; Gokeler, A (Sports Med)

The Effects of Instruction Exercises on Performance and Kinetic Factors Associated With Lower-Extremity Injury in Landing After Volleyball Blocks. - Rostami, A; Letafatkar, A; Gokeler, A; Khaleghi Tazji, M (J Sport Rehabil)

Correction to: Principles of Motor Learning to Support Neuroplasticity After ACL Injury: Implications for Optimizing Performance and Reducing Risk of Second ACL Injury. - Gokeler, A; Neuhaus, D; Benjaminse, A; Grooms, DR; Baumeister, Jochen (Sports Med)

Trunk and hip control neuromuscular training to target inter limb asymmetry deficits associated with anterior cruciate ligament injury. - Sabet, S; Letafatkar, A; Eftekhari, F; Khosrokiani, Z; Gokeler, A (Phys Ther Sport)

Test-retest reliability and discriminative ability of forward, medial and rotational single-leg hop tests. - Dingenen, B; Truijen, J; Bellemans, J; Gokeler, A (Knee)

Cross-education does not improve early and late-phase rehabilitation outcomes after ACL reconstruction: a randomized controlled clinical trial. - Zult, T; Gokeler, A; van Raay, JJAM; Brouwer, RW; Zijdewind, I; Farthing, JP; Hortobágyi, T (Knee Surg Sports Traumatol Arthrosc)

Progressive strength training restores quadriceps and hamstring muscle strength within 7 months after ACL reconstruction in amateur male soccer players. - Welling, W; Benjaminse, A; Lemmink, K; Dingenen, B; Gokeler, A (Phys Ther Sport)

Effect of playing position and time on-court on activity profiles in german elite team handball - Büchel, D; Jakobsmeyer, R; Döring, M; Adams, M; Rückert, U; Baumeister, Jochen (International Journal Performance Analysis in Sports)

Effects of different visual conditions on standing balance in a virtual reality scene: a pilot study - Vogt, S; Neuhaus, D; Baumeister, Jochen (Sportmotorik 2019. Adaptation, Lernen und virtuelle Welten)

Effects of an augmented reality training using a myoelectric hand prosthesis: a pilot study - Neuhaus, D; Vogt, S; Boschmann, A; Dosen, S; Baumeister, Jochen (Sportmotorik 2019. Adaptation, Lernen und virtuelle Welten)

A preliminary prospective Analysis of electrocortical signatures underlying ACL injury - Bonnette, S; Diekfuss, JA; Barber Foss, KD; DiCesare, CA; Riley, MA; Riehm, C; Moore, C; Grooms, DR; Myer, GD; Baumeister, Jochen

Muscle activity patterns in imitation ski jumps - Claussen, L; Baumeister, Jochen; Braaten, S; Ettema, G (Book of abstracts - German Exercise Science and Training conference)

Effect of age on reactive multidirectional speed in highly trained youth soccer players - Büchel, D; Lehmann, T; Baumeister, Jochen (Book of abstracts - German Exercise Science and Training conference)

Sports-specific differences in reactive multidirectional speed in tema sports athletes using the Speedcourt - Büchel, D; Döring, M; Berkel, F; Baumeister, Jochen (Book of abstracts - German Exercise Science and Training conference)

Negative Emotion and Joint-Stiffness Regulation Strategies After Anterior Cruciate Ligament Injury. - An, YW; Lobacz, AD; Baumeister, Jochen; Rose, WC; Higginson, JS; Rosen, J; Swanik, CB (J Athl Train)

Virtual reality interventions for balance prevention and rehabilitation after musculoskeletal lower limb impairments in young up to middle-aged adults: A comprehensive review on used technology, balance outcome measures and observed effects. - Vogt, Sarah; Skjæret-Maroni, N; Neuhaus, D; Baumeister, Jochen (Int J Med Inform)

Phase Coupling of Bilateral Motor Areas Decreases from Bipedal to Single Leg Stance - Lehmann, Tim; Büchel, Daniel; Cockcroft, John; Louw, Quinette; Baumeister, Jochen

Principles of Motor Learning to Support Neuroplasticity After ACL Injury: Implications for Optimizing Performance and Reducing Risk of Second ACL Injury. - Gokeler, Alli; Neuhaus, D; Benjaminse, A; Grooms, DR; Baumeister, Jochen (Sports Med)

Neuroplastic changes in anterior cruciate ligament reconstruction patients from neuromechanical decoupling. - An, YW; DiTrani Lobacz, A; Lehmann, T; Baumeister, Jochen; Rose, WC; Higginson, JS; Rosen, J; Swanik, CB (Scand J Med Sci Sports)

Test-retest reliability and discriminative ability of forward, medial and rotational single-leg hop tests. - Dingenen, B; Truijen, J; Bellemans, J; Gokeler, A (Knee)

Phase Coupling of Bilateral Motor Areas Decreases from Bipedal to Single Leg Stance - Lehmann, Tim; Büchel, Daniel; Cockcroft, John; Abegail Louw, Quinette; Baumeister, Jochen

Effects of Acute Physical Exercise With Low and High Cognitive Demands on Executive Functions in Children: A Systematic Review - Paschen, Linda; Lehmann, Tim; Kehne, Miriam; Baumeister, Jochen (Pediatric Exercise Science)
Purpose : Whereas many studies addressed the relation between acute physical exercise and executive functions (EF) in children, the effects of various modalities of acute exercise on EF still remain unclear. This systematic review investigated the effects of exercise with low and high cognitive demands on speed of processing and accuracy of performance in tasks examining inhibition, working memory, and cognitive flexibility in children. Method : A systematic literature research in electronic databases was performed. Controlled trials assessing the effects of acute exercise on EF in a pre–post design were included. Results : Ten studies involving a total of 890 participants revealed positive effects in working memory performance in speed of processing after acute exercises with low cognitive demands compared with seated rest, mixed results for inhibition after exercises with low and high cognitive demands, and mixed results for cognitive flexibility with low cognitive demands. Concerning accuracy, only mixed results were found for inhibition after exercises with low and high cognitive demands. Conclusion : The differentiated effects of acute exercises with low and high cognitive demands led to more positive effects in speed of processing compared with accuracy of performance. Further investigations including assessment of neurophysiological parameters of EF are needed.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; Pediatrics; Perinatology and Child Health

Effects of Acute Physical Exercise With Low and High Cognitive Demands on Executive Functions in Children: A Systematic Review. - Paschen, Linda; Lehmann, Tim; Kehne, Miriam; Baumeister, Jochen (Pediatr Exerc Sci)

A novel approach to enhance ACL injury prevention programs. - Gokeler, A; Seil, R; Kerkhoffs, G; Verhagen, E (J Exp Orthop)

Cross-education does not accelerate the rehabilitation of neuromuscular functions after ACL reconstruction: a randomized controlled clinical trial. - Zult, T; Gokeler, A; Raay JJAM, van; Brouwer, RW; Zijdewind, I; Farthing, JP; Hortobágyi, T (Eur J Appl Physiol)

Angle-specific analysis of isokinetic quadriceps and hamstring torques and ratios in patients after ACL-reconstruction. - Baumgart, C; Welling, W; Hoppe, MW; Freiwald, J; Gokeler, A (BMC Sports Sci Med Rehabil)

Transfer of improved movement technique after receiving verbal external focus and video instruction. - Benjaminse, A; Welling, W; Otten, B; Gokeler, A (Knee Surg Sports Traumatol Arthrosc)

The effect of load on Achilles tendon structure in novice runners. - Heyward, OW; Rabello, LM; van der Woude, L; van den Akker-Scheek, I; Gokeler, A; van der Worp, H; Zwerver, J (J Sci Med Sport)

Let us rethink research for ACL injuries: a call for a more complex scientific approach. - Gokeler, A; Verhagen, E; Hirschmann, MT (Knee Surg Sports Traumatol Arthrosc)

The Relationship between Sensory Responses to Ankle Joint Loading and Corticomotor Excitability - Needle, AR; Baumeister, Jochen; Farquahr, WB; Greaney, JL; Higginson, JL; Kaminski, TW; Swanik, CB (Int J Neuroscience)

Low rates of patients meeting return to sport criteria 9 months after anterior cruciate ligament reconstruction: a prospective longitudinal study - Welling, W; Benjaminse, A; Seil, R; Lemmink, K; Zaffagnini, S; Gokeler, A (Knee Surg Sports Traumatol Arthrosc)

Nonoperative treatment of muscle injuries - recommendations from the GOTS expert meeting - Hotfiel, T; Seil, R; Bily, W; Bloch, W; Gokeler, A; Krifter, RM; Mayer, F; Ueblacker, P; Weisskopf, L; Engelhardt, M (J Exp Orthop)

Altered movement during single leg hop test after ACL reconstruction: implications to incorporate 2-D video movement analysis for hop test - Welling, W; Benjaminse, A; Seil, R; Lemmink, K; Gokeler, A (Knee Surg Sports Traumatol Arthrosc)

Comparison of postural stability in the ACL deficient and reconstructed leg: a Meta analysis - Lehmann, T; Paschen, Linda; Baumeister, Jochen

Negative emotional stimuli increase neurocognitive processing in the brain - An, YW; DiTrani Lobacz, A; Baumeister, Jochen; Swanik, CB

Exploring Functional Brain Connectivity of Postural Control in Upright Stance - Lehmann, T; Büchel, D; Cockcroft, J; Louw, QA; Baumeister, Jochen (Proceedings of the 3rd International Mobile Brain/Body Imaging Conference)

Effect of a cognitive dual-task on electrocortical activation during single leg stance - Büchel, D; Lehmann, T; Cockcroft, J; Louw, QA; Baumeister, Jochen (Proceedings of the 3rd International Mobile Brain/Body Imaging Conference)

Exergames Inherently Contain Cognitive Elements as Indicated by Cortical Processing - Anders, Phillipp; Lehmann, Tim; Müller, Helen; Grønvik, Karoline B.; Skjæret-Maroni, Nina; Baumeister, Jochen; Vereijken, Beatrix (Frontiers in Behavioral Neuroscience)

Exploring Functional Brain Connectivity of Postural Control in Upright Stance - Lehmann, Tim; Büchel, Daniel; Baumeister, Jochen

Exergames Inherently Contain Cognitive Elements as Indicated by Cortical Processing - Anders, Phillipp; Lehmann, Tim; Müller, Helen; Grønvik, Karoline B.; Skjæret-Maroni, Nina; Baumeister, Jochen; Vereijken, Beatrix (Frontiers in Behavioral Neuroscience)
Keywords: Behavioral Neuroscience; Cognitive Neuroscience; Neuropsychology and Physiological Psychology

Comparison of postural stability in the ACL-deficient and reconstructed leg: A meta analysis - Lehmann, Tim; Paschen, Linda; Baumeister, Jochen

Neuroplastic changes in anterior cruciate ligament reconstruction patients from neuromechanical decoupling - An, Yong Woo; DiTrani Lobacz, Andrea; Lehmann, Tim; Baumeister, Jochen; Rose, William C.; Higginson, Jill S.; Rosen, Jeffrey; Swanik, Charles Buz (Scandinavian Journal of Medicine and Science in Sports)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Exergames Inherently Contain Cognitive Elements as Indicated by Cortical Processing - Anders, Phillipp; Lehmann, Tim; Müller, Helen Martha; Grønvik, Karoline B.; Skjæret-Maroni, Nina; Baumeister, Jochen; Vereijken, Beatrix (Frontiers in Behavioral Neuroscience)
Keywords: Behavioral Neuroscience; Cognitive Neuroscience; Neuropsychology and Physiological Psychology

Effect of Cognitive Dual Task on Cortical Activation during Static Postural Control - Büchel, Daniel; Lehmann, Tim; Cockcroft, John; Abegail Louw, Quinette; Baumeister, Jochen

The Relationship Between Joint Stiffness and Muscle Activity in Unstable Ankles and Copers. - Needle, AR; Kaminski, TW; Baumeister, Jochen; Higginson, JS; Farquhar, WB; Swanik, CB (J Sport Rehabil)

Objective impairments of glait and balance in adults living with HIV-1 infection: a systematic review and meta-analysis of observational studies - Berner, K; Morris, L; Baumeister, Jochen; Louw, Q (BMC Musculoskelet Disord)

Altered brain activity during joint loading after anterior cruciate ligament reconstruction - An, YW; DiTrani Lobacz, A; Lehmann, T; Baumeister, Jochen; Swanik, CB

Altered cortical activation patterns following anterior cruciate ligament reconstruction during joint loading - An, YW; DiTrani Lobacz, A; Lehmann, T; Baumeister, Jochen; Swanik, CB

Balance exergames increase cortical activity in frontal areas of the brain - Anders, P; Lehmann, T; Müller, H; Molde, I; Gronvik, KB; SkaeretMaroni, N; Vereijken, B; Baumeister, Jochen

Single-Leg Assessment of Postural Stability After Anterior Cruciate Ligament Injury: a Systematic Review and Meta-Analysis. - Lehmann, T; Paschen, Linda; Baumeister, Jochen (Sports Med Open)

Single-Leg Assessment of Postural Stability After Anterior Cruciate Ligament Injury: a Systematic Review and Meta-Analysis - Lehmann, Tim; Paschen, Linda; Baumeister, Jochen (Sports Medicine - Open)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Altered Brain Activity During Joint Loading After Anterior Cruciate Ligament Reconstruction - An, Yong Woo; DiTrani Lobacz, Andrea; Lehmann, Tim; Baumeister, Jochen; Swanik, Charles Buz (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine